Effect of different bedding materials on the performance of rats (Journal of Laboratory Animal Science, 2024)
Bedding and nesting material provided in cages for laboratory rats has important consequences on welfare, directly through  the comfort and utility in behaviour such as nest building, and indirectly through properties such as air quality. A study was  conducted at Small Animal House, Veterinary College, Bangalore to find out effect of different bedding materials on the  reproductive performance of laboratory rats. Thirty Wistar female rats were divided into three groups and subjected to the  different bedding material used – paddy husk (PH), corncob (CC) and wood shavings (WS). Litter size and litter weight  were recorded at birth and at weaning (day 21). Bedding material significantly (P0.05) different from the other groups. The results indicate that wood shavings and  corncob may be suitably used as alternative to other bedding materials for laboratory rats.
Keywords: Rat; Litter weight; Litter size; Paddy husk; Corncob; Wood shavings